PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT RAMAYANA LESTARI SENTOSA TBK BEKASI TIMUR - Sandy Alviah; Lia Asmalah (Al Hasanah Barokah Foundation, 2025)
This study aims to analyze the influence of competence and work discipline on employee performance at PT Ramayana Lestari Sentosa Tbk East Bekasi. The research method used is quantitative method. The population and this study are all employees working at PT Ramayana Lestari Sentosa Tbk. The sample used was 129 respondents using saturated sampling technique. The data analysis method used simple linear regression test, multiple linear regression, correlation coefficient, determination coefficient, partial t test and simultaneous F test. The results of the study showed that: (1) There is a positive and significant influence between Competence (X1) on Employee Performance (Y) at PT Ramayana Lestari Sentosa Tbk East Bekasi, this can be proven from the t-value of 5.101> t-table 1.979 with a significant level of 0.000<0.05. (2) There is a positive and significant influence between Work Discipline on Employee Performance (Y) at PT Ramayana Lestari Sentosa Tbk East Bekasi, this can be proven from the t-value of 7.001>t-table 1.979 with a significance level of 0.000<0.05. (3) Simultaneously there is a positive and significant influence between Competence (X1) and Work Discipline (X2) on Employee Performance (Y) at PT Ramayana Lestari Sentosa Tbk East Bekasi, this can be proven from the F-value of 28.624>F-table 3.06 with a significance level of 0.000<0.05. This study confirms the positive and significant influence between competence, work discipline, and employee performance at PT Ramayana Lestari Sentosa Tbk East Bekasi, which means H0 is rejected Ha is accepted.